Estudos e análise dos voláteis das folhas de nim por clevenger e cg-em. - MONTEIRO, Elder Silva Paz. (Universidade Federal do Tocantins, 2024)
The neem tree (Azadirachtina indica A. Juss) is mainly recognized for its therapeutic, pesticide, fertilizer and pharmacological chemical properties, because of its abundance of organic compounds belonging to various chemical classes with biological activities. Due to these attributes, this neem plant has great economic potential and continues to be used worldwide. In the present work, the extraction and chemical characterization of oil from neem leaves collected at the Universidade Federal Norte do Tocantins (UFNT) campus Cimba, located in Araguaína, Tocantins, was carried out. For oil extraction, the Clevenger system was used, while for the extraction and characterization of volatiles, the HS-MEFSCG-EM method was used. The average yield obtained from the oil was 0.3g of neem essential oil. Compared to neem seed oil, this yield is lower, however for the analyzes carried out it was satisfactory. A total of 52 volatile compounds were detected, of which 5 were identified by Kovats index: ethyl acetate, 96.3%; (E)-1(prop-1-em-1-yl) -3-propyltrisufane, 76.6%; n-hexano, 62.7%; 2,4-hexenol, Z, 68.9%; 2- Cyclopenten-one, 2-methyl, 60.%. Some volatiles have had their bioactivities reported and correspond with the known benefits of neem. Thus, these chemical constituents are considered part of the synergistic effect on the plant.